THE APPLICATION OF THE COOPERATIVE STORY TYPE COOPERATIVE METHOD IN LEARNING WRITE SHORT STORIES - Irma Charlin Oktaviani; Ika Mustika; Rochmat Tri Sudrajat (IKIP Siliwangi, 2021)
One of the teaching materials that high school students learn is writing short story texts. In the learning process, there are problems experienced by students, including difficulties in finding ideas and developing stories. The formulation of the research problems: 1) how is the implementation of the cooperative method of storytelling in pairs on short story writing material? and 2) how is the pre-test and post-test scores for the experimental and control classes? This study shows the implementation of the cooperative method of storytelling in pairs is carried out in accordance with the Learning Implementation Plan. The research method is a quasi-experimental quantitative approach. The research stages were pre-test, giving treatment, and post-test. The results showed that the experimental class average score increased after using the cooperative method of telling pair stories. The pre-test average score was 56, increased in the post-test to 80, so the students' writing ability in the experimental class had a significant increase. Meanwhile, the mean value of the control class increased but not significantly. The pre-test average score was 52, increasing in post-test to 64. It can be concluded that the cooperative method of storytelling in pairs can be used in short story writing learners.